Consentimiento informado en medicina Anticonceptiva, interrupción voluntaria del embarazo y ecografía prenatal en Colombia (2021)
Informed consent requires a positive and active attitude for the health service provider and a willingness committed to the patient from whom it is sought to achieve a device act of authentic will-autonomy, in which it is possible to prevent risks, alternatives, disadvantages and conditions of success of the contraceptive treatment singularly considered; total transparency and impartiality in the case of voluntary interruption of pregnancy and, timeliness and fairness with respect to the means of prenatal diagnosis, for which 1t is necessary to observe the jurisprudential sub-rules elaborated by the Constitutional Court and the Colombian Council of State, in harmony with the constitutional principles and international standards that regulate the matter.